Pengembangan Sistem Informasi Penilaian Berbasis Web Menggunakan Metode Waterfall (Studi Kasus SDN Pamulang Indah) - Fiqih Wijaya; Sartika Lina Mulani Sitio (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
In the learning system, of course, there is an assessment of how well and how well the students understand the material that the teacher provides each semester. However, teachers and administrative staff often find it difficult to input existing values due to technological limitations, so they still manually input values on the paper given to each field teacher and then input by the administration staff into the system. Of course, this method is prone to human error and also takes a very long time. The method used was in the form of observation and direct interviews by the informants related to this problem, of course I have also asked permission first from the principal in this school. By making a scoring system that is directly connected to the system, it will simplify the tasks of administrative staff and field teachers in inputting the grades of their students so there is no need to work twice and re-enter existing data. It is enough to provide access to field teachers to fill in the scores according to the form provided and the automated data will be updated by the system in real time. In conclusion, this assessment system facilitate the work of teachers in the field of study in inputting grades and administrative staff who do not need to work twice, of course it will also minimize human error and errors in inputting existing data, especially when the data is important and crucial considering the grades of this school student.